Canola Cost-Return Budget in South Central Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2004)
This publication contains information for a projected budged reflecting expected income and cost based on canola production practices in south central Kansas.
MF2421_2004_10
Keywords: MF2421; Crops; Economics; MF